Non-Formal Islamic Education in Shaping the Religious Character of Urban Communities in Sekarbela and Pesinggahan, Mataram City - Zulkifli; Fahrurrozi, Muhammad; Sari, Ratna Permata (Universitas Islam Negeri Raden Intan Lampung, 2025)
The objectives of this study are: (1) to explain the concept and implementation of kitab turats learning in Sekarbela and Pesinggahan, Mataram City; and (2) to explain the contribution of kitab turats learning in Sekarbela and Pesinggahan, Mataram City, as a form of non-formal Islamic education in shaping the religious character of urban communities. This study employs a qualitative and multidisciplinary approach. Data were collected through observation, interviews, and documentation. The data analysis technique uses Spradley’s ethnographic qualitative analysis model, in which data analysis is conducted directly in the field simultaneously with the data collection process. The analysis consists of domain analysis, taxonomic analysis, componential analysis, and thematic analysis. The results show that kitab turats learning in Sekarbela was initiated by TGH Muhammad Rais, while in Pesinggahan it was pioneered by TGH Mustofa Kamal. The implementation of kitab turats learning has been smooth and successful due to support from knowledgeable teachers, diligent students, comprehensive learning objectives, holistic learning materials, and varied methods, including thariqah ‘alaniyah, which focuses on the material–cognitive domain, and thariqah sirriyah, which encompasses spiritual–affective aspects. In addition, learning evaluation is integrative, combining cognitive, psychomotor, and affective domains. Kitab turats learning in Sekarbela and Pesinggahan, Mataram City, makes a significant contribution to shaping the religious character of urban communities.